Mesenchymal transition and increased therapy resistance of glioblastoma cells is related to astrocyte reactivity. Issue 3 (31st August 2019) - Niklasson, Mia; Bergström, Tobias; Jarvius, Malin; Sundström, Anders; Nyberg, Frida; Haglund, Caroline; Larsson, Rolf; Westermark, Bengt; Segerman, Bo; Segerman, Anna
Abstract: Grade IV astrocytoma/glioblastoma multiforme (GBM) is essentially incurable, partly due to its heterogenous nature, demonstrated even within the glioma‐initiating cell (GIC) population. Increased therapy resistance of GICs is coupled to transition into a mesenchymal (MES) cell state. The GBM MES molecular signature displays a pronounced inflammatory character and its expression vary within and between tumors. Herein, we investigate how MES transition of GBM cells relates to inflammatory responses of normal astroglia. In response to CNS insults astrocytes enter a reactive cell state and participate in directing neuroinflammation and subsequent healing processes. We found that the MES signature show strong resemblance to gene programs induced in reactive astrocytes. Likewise, astrocyte reactivity gene signatures were enriched in therapy‐resistant MES‐like GIC clones. Variable expression of astrocyte reactivity related genes also largely defined intratumoral GBM cell heterogeneity at the single‐cell level and strongly correlated with our previously defined therapy‐resistance signature (based on linked molecular and functional characterization of GIC clones). In line with this, therapy‐resistant MES‐like GIC secreted immunoregulatory and tissue repair related proteins characteristic of astrocyte reactivity. Moreover, sensitive GIC clones could be made reactive through long‐term exposure to the proinflammatory cytokine interleukin 1 beta (IL1β). IL1β induced a slow MES transition, increased therapy resistance, and a shift in DNA methylation profile towards that of resistant clones, which confirmed a slow reprogramming process. In summary, GICs enter through MES transition a reactive‐astrocyte‐like cell state, connected to therapy resistance. Thus, from a biological point of view, MES GICs would preferably be called 'reactive GICs'. The ability of GBM cells to mimic astroglial reactivity contextualizes the immunomodulatory and microenvironment reshaping abilities of GBM cells that generate a tumor‐promoting milieu. This insight will be important to guide the development of future sensitizing therapies targeting treatment‐resistant relapse‐driving cell populations as well as enhancing the efficiency of immunotherapies in GBM. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.